Removing of heavymetals from water by chitosan nanoparticles (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Chitosan was prepared by deacetylation of chitin. The prepared chitosan has characterized bymolecular weight, degree of deacetylation, and ash %. Chitosan nanoparticles were prepared byionotropic gelation of chitosan with tripolyphosphate anions. The structure and particle size of chitosan nanoparticles have confirmed via FTIR analysis and TEM imaging.The chitosan nanoparticles were used in water treatment to remove metal ions from sample contains 20 ppm from each Fe+2, Mn+2, Zn+2 and Cu+2.The optimum conditions for this study were at 2 g/l of chitosan nanoparticles, pH 7 and 30 min of mixing time. Chitosan showed the highest performance under these conditions with removing percent 99.94% 80.85% 90.49% and 95.93% from Fe+2, Mn+2, Zn+2 and Cu+2 respectively.